Optimizing Income Tax Revenue: The Roles of Taxpayer Compliance, Audit Effectiveness, and Payment Timeliness - Zaki, Yusuf Abdurrahman; Sari, Imelda (Santoso Academy Network, 2025)
This study examines the impact of taxpayer compliance, tax audits, and income tax payable both independently and collectively on income tax revenue at the Penjaringan Primary Tax Office in Jakarta. Utilizing a quantitative approach, the analysis employs multiple linear regression, t-tests, and F-tests on data from corporate taxpayers. The results reveal that taxpayer compliance, the effectiveness of tax audits, and the amount of income tax payable each have a positive and significant effect on income tax revenue, with tax audits contributing the most significantly. Together, these variables account for 70.8% of the variation in income tax revenue. The originality of this research lies in its comprehensive exploration of compliance behavior, audit enforcement, and payment realization within a single administrative context, providing empirical evidence from a densely populated urban tax office that has been previously overlooked in the literature. The practical implications underscore the necessity for tax authorities to enhance compliance monitoring systems, strengthen risk-based audit frameworks, and improve the management of tax receivables to elevate the effectiveness of income tax administration and mitigate revenue leakage